CONVIVIAL IN THE NOVEL THE STARS SHINE DOWN BY SIDNEY SHELDON (A PRAGMATICS ANALYSIS) - Silvia Sangeroki (Jurnal Akrab Juara, 2019)
This study is focused on one aspect of speech act that is convivial act. Convivial is one part of speech act belongs to pragmatic study. Speech act consists of locutionary act, illocutionary act and perlocutionary act. This research was done through descriptive method. Data has been taken from the utterances that are produced by the characters in the novel. The collected data were analyzed descriptively based on Leech’s theory. The result of this research shows that the kinds and functions of convivial act in the novel The Stars Shine Down by Shidney Sheldon can be categorized into six aspects, those are offering,compliment, greeting, commiserate, inviting and thanking.